Pertumbuhan Dan Hasil Dua Varietas Jagung Hibrida Sebagai Tanaman Sela Dibawah Tegakan Karet - Mahdiannoor Mahdiannoor; Nurul Istiqomah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
Corn is one commodity that has a strategic role and economical. In Indonesia, the corn cultivated in diverse environments. Rubber is one of the most important plantation crop in South Kalimantan, rubber plantations people usually managed with simple cultivation techniques. Planting corn as intercrops among plantation crops made to utilize the available land, especially in staple crops are not produced. The research was conducted in the Galumbang Village RT III, Paringin Selatan District, Balangan Regency South Kalimantan Province, for 4 months, from May to July 2014. This experiment using a randomized block design with two treatments. The treatments tested were two varieties of sweet corn (B), namely (b1) Jago F1 and (b2) Bonanza F1. Each treatment comprised 12 plants and 16 replications so that overall there are 192 plants with 2 plant samples. Results of analysis of variance showed that the growth and yield of two varieties of sweet corn hybrids as intercrops under the rubber stands significant effect on plant height observation variables aged 28, 35 and 42 days after planting (DAP); variable number of leaf age 28 and 35 DAP; variable diameter stems of plants aged 28, 35, 42 and 49 DAP; and the variable length of the cob without husk of corn. Likewise, no effect on plant height observation variables age 49 DAP; variable number of leaf age 42 and 49 DAP; variables wet weight cob with husk; variables wet weight without husk; and the diameter of the cob without husk. Two variables observation that can not be done analysis of variance that are number of samples per plot and number of cobs per plant samples. Based The DMRT test the best treatment is sweet corn Bonanza F1 (b2) varieties.